Infrared and Raman spectroscopic characterization of the hydrogen-bonding network in l-serine crystal - Jarmelo, S. (2007)
The IR spectra (4000-400 cm-1) of neat and isotopically substituted (ND/OD <= 10% D and [congruent with]30% D) polycrystalline l-serine ([alpha]-amino-[beta]-hydroxypropionic acid; HO-CH2-CH(NH3)+-COO-) were recorded in the temperature range 300-10 K and assigned. The isotopic-doping/low-temperature methodology, which allows for decoupling of individual proton vibrational modes from the crystal bulk vibrations, was used for estimating the lengths and energies of the different H-bonds present in l-serine crystal. To this end, the frequency shifts observed in both the NH/OH stretching and out-of-plane bending spectral regions (relatively to reference values for these vibrations in non-hydrogen-bonded l-serine molecules) were used, together with previously developed empirical correlations between these spectral parameters and the H-bond properties. In addition, the room-temperature Raman spectrum (4000-150 cm-1) of a single crystal of neat l-serine was also recorded and interpreted. A systematic comparison was made between the spectroscopic data obtained currently for l-serine and previously for dl-serine, revealing that the vibrational spectra of the two crystals reflect well the different characteristics of their hydrogen-bond networks, and also correlate accurately with the different susceptibility of the two crystals to pressure-induced strain.